2012
DOI: 10.1002/eco.1254
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater‐dependent distribution of vegetation in Hailiutu River catchment, a semi‐arid region in China

Abstract: In arid and semi‐arid regions, groundwater availability is one of the controls on vegetation distribution. This groundwater‐dependent distribution of vegetation has been particularly observed in the Hailiutu River catchment, a semi‐arid region in North China. We used remote sensing images of vegetation index (normalized difference vegetation index, NDVI) and field data of depth to water table (DWT) to assess the response of vegetation distribution on increase of DWT at the regional scale. The frequency distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 12 publications
2
40
0
Order By: Relevance
“…Thus, plant density tends to be larger when groundwater is available than in nearby vegetation that does not have access to groundwater. Lv et al (2012) used a remotely sensed vegetation index (normalised difference vegetation index; NDVI; 300 m resolution) to examine changes in depth-to-groundwater within a small region in northern China. NDVI is a reliable measure of the chlorophyll content ("greenness") in leaves and vegetation cover (Gamon et al, 1995;Carlson and Ripley, 1997;Huete et al, 2002).…”
Section: Satellite-based Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, plant density tends to be larger when groundwater is available than in nearby vegetation that does not have access to groundwater. Lv et al (2012) used a remotely sensed vegetation index (normalised difference vegetation index; NDVI; 300 m resolution) to examine changes in depth-to-groundwater within a small region in northern China. NDVI is a reliable measure of the chlorophyll content ("greenness") in leaves and vegetation cover (Gamon et al, 1995;Carlson and Ripley, 1997;Huete et al, 2002).…”
Section: Satellite-based Approachesmentioning
confidence: 99%
“…Similarly, increased Huber value, (Table 3). Consequently, response functions for individual traits are readily apparent; examples include changes with depth-to-groundwater in rates of photosynthesis (Horton et al, 2001), plant cover (Elmore et al, 2006), NDVI (Lv et al, 2012) and crown dieback (Horton et al, 2001). However, few studies have examined multiple traits across multiple scales and then provided an integrated "ecosystem-scale" response function to differences in groundwater availability.…”
Section: Multiple Traits Across Leaf Branch Whole-tree and Standmentioning
confidence: 99%
“…When groundwater is available to vegetation, plant density tends to be larger than adjacent areas where groundwater is unavailable. Lv et al (2012) used remotely sensed images of a vegetation index (the Normalised Difference Vegetation Index; NDVI) to assess changes in NDVI as a function of depth-togroundwater in northern China. A 25 m resolution digital elevation model and groundwater bore data were used to generate a contour map of groundwater depths across the 2600 km 2 catchment.…”
Section: Application Of Vegetation Indices Derived From Rsmentioning
confidence: 99%
“…However, apart from the influence of climatic change, NDVI is also strongly related to the groundwater table level (GTL) in arid and semi-arid regions [2,[17][18][19]. Many investigators have also reported the relationship between vegetation and groundwater availability (Lv et al, 2013;Jin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Jin et al (2016) found a linear correlation between NDVI and groundwater depth in the Qaidam basin [2]. The distribution of GTL is becoming more heterogeneous in the middle reaches of Hei River as a result of increasing cultivated land area and runoff from Yingluo station [18]. The distribution of vegetation is also highly heterogeneous and depends on multiple factors.…”
Section: Introductionmentioning
confidence: 99%